Prognostic significance of the novel nutrition-inflammation marker of lymphocyte–C-reactive protein ratio in patients with nasopharyngeal carcinoma receiving concurrent chemoradiotherapy - Xin Hua; Zhi-Qing Long; Si-Fen Wang; Fei Xu; Meng-Di Wang; Jia-Yi Chen; Yu-Ling Zhang; Wei-Qiong Ni; Yun-Sheng Gao (Frontiers in Nutrition, 2023)
BackgroundRecent studies indicate that the novel lymphocyte–C-reactive protein ratio (LCR) is strongly associated with the survival of various tumors, but its prognostic value in nasopharyngeal carcinoma (NPC) is understudied. This study aimed to explore the relationship between LCR and overall survival (OS) in NPC and develop a predictive model.MethodsA total of 841 NPC patients who received concurrent chemoradiotherapy (CCRT) between January 2010 and December 2014 were retrospectively enrolled and randomly divided into a training cohort (n = 589) and a validation cohort (n = 252), and 122 patients between January 2015 and March 2015 were included as an additional validation cohort. Univariate and multivariate Cox analyses were performed to identify variables associated with OS and construct a predictive nomogram. The predictive accuracy of the nomogram was evaluated and independently validated.ResultsThe LCR score differentiated NPC patients into two groups with distinct prognoses (HR = 0.53; 95% CI: 0.32–0.89, P = 0.014). Multivariate analysis showed that age, T stage, N stage, EBV-DNA status, and LCR score were independently associated with OS, and a predictive nomogram was developed. The nomogram had a good performance for the prediction of OS [C-index = 0.770 (95% CI: 0.675–0.864)]. and outperformed the traditional staging system [C-index = 0.589 (95% CI: 0.385–0.792)]. The results were internally and additionally validated using independent cohorts.ConclusionThe pretreatment LCR could independently predict the overall survival in NPC patients. A novel LCR-based prognostic model of an easy-to-use nomogram was established, and it outperformed the conventional staging system in terms of predictive power. Further external verification remains necessary.